THE INFECTION PROCESS OF Fusarium subglutinans IN Pinus merkusii SEEDLINGS - Widyastuti, S. M.; Christita, M.; Harjono, Harjono; Christanti, S. (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2014)
Pinus merkusii or tusam is an original Indonesian plant and it is naturally distributed in Aceh and North Sumatra. Damping-off disease is the main problem in its nurseries. Fusarium subglutinans is one of the leading causes of damping-off disease. The knowledge of fungal infections process of tusam seedlings is essential to control damping- off disease effectively.The aim of this research is to understand (1) infection process of F. subglutinans in tusam seedlings and the defence response of seedlings against the infection of F. subglutinans. The methods used in this research were (1) identification of fungal pathogens that causing the disease, (2) pathogenicity test of F.Â subglutinans, (3) detection the accumulation of lignin, accumulation of callose and hypersensitive reactions by staining of seedling tissue using phloroglucinol, aniline blue and lactophenol trypan blue.The results of this study revealed that spores germination occurred in two days after inoculation. Direct penetration through cell wall and stomata was observed on the third day after inoculation. There was hypersensitive reaction in stomata. Accumulation of callose and lignin appeared on the third day after inoculation. However, defence response of seedlings was not effective, as F. subglutinans is a necrotroph fungus.Keywords: damping-off, Fusarium subglutinans, Pinus merkusii, tusam